Novel ball-type four dithioerythritol bridged metallophthalocyanines and their water-soluble derivatives: Synthesis and characterization, and electrochemical, electrocatalytic, electrical and gas sensing properties - ÖZKAYA, ALİ RIZA (ROYAL SOC CHEMISTRY, 2010)
The phthalodinitrile derivative 3 was prepared by the reaction of 1,4-dithioerythritol 1 and 4-nitrophthalonitrile 2 in dry DMF as the solvent in the presence of K2CO3 as the base by the method of nucleophilic substitution of an activated nitro group in an aromatic ring. The template reaction of compound 3 with the corresponding metal salts gave the novel binuclear MPcs of ball-type (M = Zn 4, Co 5, Cu 6) and their water soluble phthalocyanines 7-9 were obtained from refluxing a suspension of the compounds bearing eight OH side groups, in aqueous NaOH (%30) solution. Newly synthesized compounds were characterized by elemental analysis, UV/VIS, IR, MALDI TOF mass and H-1-NMR spectroscopy techniques. The electronic spectra exhibit an intense pi ->pi* transition of characteristic Q and B bands of the phthalocyanine core. The electrochemical measurements showed the formation of various mixed-valence oxidation and reduction species of 4 and 6 due to weak intramolecular interactions between the two MPc units. Complex 5 displayed a much higher catalytic activity than those of 4 and 6. It was found that oxygen reduction on the 5-based catalyst occurs through a direct 4-electron transfer pathway with a high water selectivity. However, the overpotential for oxygen reduction is high, probably due to a long distance between the two CoPc units in 5. A. c. and d.c. conductivity measurements were performed as a function of temperature (300-543 K) and frequency (40 10(5) Hz). It was found from d.c. measurements that the values of the pre-exponential factor sigma(0) for the investigated samples are in the interval from 1.36 x 10(-3) to 6.20 x 10(2) Omega(-1) cm(-1), inferring that the conduction occurs most probably by hopping between the localized states in band tails. Based on the existing theory of a. c. conduction, it has been concluded that for the low frequency region the dominant conduction mechanism is multihopping at high temperatures (>390 K) whereas for the high frequency region the correlated barrier hopping model is the dominant mechanism. The sensing properties of the films for CO2 gas were also investigated.
Keywords: ETHER-SUBSTITUTED PHTHALOCYANINES; HETERO-DINUCLEAR PHTHALOCYANINES; LANGMUIR-BLODGETT-FILMS; OXYGEN REDUCTION; COBALT PHTHALOCYANINES; ZINC PHTHALOCYANINES; METAL-FREE; ELECTROCHROMIC PROPERTIES; COPPER PHTHALOCYANINE; COMPLEXES